Tourism Suitability Index (TSI) and Regional Carrying Capacity (RCC) of Pesona Beach in Teluk Rhu Village, North Rupat Bengkalis Regency, Riau - Merry Manalu; Trisla Warningsih; Darwis AN (Faculty of Fisheries and Marine, Universitas Riau, 2023)
Rupat island in Riau Province has many beaches as tourist destinations. One of the beaches is Pesona Beach which is located in Teluk Rhu village, North Rupat, Riau Province. This beach has the beauty of white sand that stretches along the coast. This study was conducted in July 2021 with the aim of knowing the tourism suitability index and calculating the carrying capacity of the region to develop into a beach tourism destination. This research method used descriptive and qualitative method then the data is based on the parameters of the Tourism Suitability Index (TSI) and Regional Carrying Capacity (RCC). The final results showed that the tourism suitability index for four categories: beach recreation S2 (appropriate), swimming S2 (appropriate), fishing S1 (very suitable), and boating S1 (very suitable). The regional carrying capacity of the Pesona beach area for tourism activities can accommodate 821 people/day. If there is an excess of visitors, it will have a negative impact on the ecosystem, therefore it is necessary to pay attention to the operation of the tourist area so that it is preserved and sustainable.